Disruptive technologies in cardiac surgery and interventional cardiology - Serdar Janjuš, Slavica; Bergsland, jacob (Scripta Medica, 2020)
The last several decades have witnessed a huge expansion of surgical and interventional treatment of cardiac disease. Axel Cappelen from Oslo, Norway was one of the first to operate on the heart, something that had until then, been considered foolish and without chance of success. (1). Cappelen dared to operate on the heart in spite of Billroth’s stark warning against such “unwise” attempts as he ligated a bleeding coronary artery caused by a stabbing injury. Most of the innovation in recent years has been within the interventional cardiology domain in contrast to the first 7 decades of the 20.century, when surgeons dominated. Cardiac surgeons have developed less invasive procedures, although the most common surgical incision is based on the time-honored and large median sternotomy incision. Many surgeons continue to prefer the concept of “Grosse Chirurgen, Grosse Schnitte” and have stayed away from minimization and continue to use direct vision, usually augmented by magnification glasses, median sternotomy and cardiopulmonary bypass (CPB). However new technology has made the need for CPB less important (2). In this article we will describe a selection of recently developed devices for cardiac intervention.